Endometriosis does not confer improved prognosis in ovarian clear cell carcinoma: a retrospective study at a single institute - Ting Zhao; Yu Shao; Yan Liu; Xiao Wang; Luyao Guan; Yuan Lu (BMC, 2018)
Abstract Background Considered as the precursor lesion of a subset of ovarian clear cell carcinoma (OCCC), the prognostic role of endometriosis in OCCC patients remains controversial. This study aimed to investigate the prognostic role of coexisting endometriosis in the survival of patients with OCCC, and also sought to identify other prognostic factors. Results A total of 125 patients were diagnosed with OCCC during the study period. Of these, 55 (44.0%) patients had coexisting endometriosis. Patients with endometriosis were younger (p = 0.030), had smaller tumor diameter (p = 0.005) and lower preoperative CA125 levels (p = 0.005). More patients with endometriosis had International Federation of Gynecology and Obstetrics (FIGO) stage I disease (83.6% vs. 51.4%, p = 0.000) and exhibited sensitivity to platinum-based regimen (89.6% vs. 66.7%, p = 0.003). Univariate and multivariate analysis revealed that coexisting endometriosis was not a predictor of 5-year overall survival (OS) or progression-free survival (PFS) of OCCC patients. For OS, chemosensitivity was the only useful prognostic factor (Hazards ratio (HR) 109.33, 95% Confidence Interval (CI) 23.46-511.51; p = 0.000). For PFS, the useful prognostic factors were ascites (HR 2.78, 95% CI 1.21-6.47; p = 0.016), FIGO stage (HR 1.61, 95% CI 1.04-2.49; p = 0.033), and chemosensitivity (HR 101.60, 95% CI 29.45-350.49; p = 0.000). Moreover, higher FIGO stage was the only risk factor for resistance to platinum-based chemotherapy (Exp (B) = 0.292, 95% CI 0.123-0.693; p = 0.005). Conclusions In this study, coexisting endometriosis was not a prognostic factor for the survival of OCCC patients. The most important predictor of both 5-year OS and PFS was chemosensitivity to platinum-based regimen, which decreased significantly with increase in FIGO stage.